Does Growth & Quality of Capital Markets drive Foreign Capital? The case of Cross-border Mergers & Acquisitions from leading Emerging Economies - Juan Pi\~neiro Chousa; Artur Tamazian; Krishna Chaitanya Vadlamannati (Turkish Economic Association, 2008)
Is there any interrelationship between firm level FDI in the form of cross border Mergers & Acquisitions and capital markets growth and quality? We addressed this question using panel data of cross border M&A for nine emerging economies. Our study period goes from 1987 to 2006. We find that the stock market variables, viz., capitalization and value addition encourage the number of deals and value of cross border Mergers & Acquisitions. However, the association with regulatory and financial reforms is much stronger and robust. We then interact both the stock market variables with financial and regulatory reforms variables only to find much stronger results. The coefficients proved to be higher than other variables, suggesting that higher reforms in capital markets could increase firm level FDI. Moreover, the results are found to be extremely robust when we replace stock market variables with squared values of the same, reiterating the fact that larger is the growth, greater is the inflow of firm level FDI in the form of cross border Mergers & Acquisitions.
Keywords: E44; M16; O53; O54; O55; 330; Financial Markets; Cross border M&A & Emerging Economies; Finanzmarkt; Finanzmarktregulierung; Direktinvestition; Übernahme; Aufstrebende Märkte; Schwellenländer